A Review of the Molecular Interaction between Plant Polyphenols and Starch - Nan CHEN; Haoxiang GAO; Qiang HE; Weicai ZENG (Shipin gongye ke-ji, 2023)
Starch is the important raw material for food industry, and it is also the main bioenergy source for human body. Plant polyphenols are a kind of active substances that widely exist in plants, and they are beneficial to human health. And the molecular interaction between plant polyphenols and starch can affect the quality (such as texture, flavor, color and so on) and nutrition of starch food during processing and storage. On the basis of consulting a lot of literature and studies, this paper reviews the molecular interaction between plant polyphenols and starch and its influence on the related properties of starch and plant polyphenols, these include the formation of complexes between plant polyphenols and starch (including V-type inclusion facilitated by hydrophobic effect and complex most through hydrogen bonds), the change of their interaction on the physicochemical properties (such as pasting, retrogradation, rheological properties, etc.), microstructure and digestive properties of starch, as well as the effect of protection and slow release on plant polyphenols, which would provide useful guidance for the resource utilization of plant polyphenols in starch processing and storage and other related fields.